Implementation of Queue Tree and DoH on Mikrotik Router for Internet Sehat and Stable Internet - Lucky Mangkey; Daniel Raymod Mangkey (Jurnal Informasi dan Teknologi, 2025)
This study presents the implementation of Queue Tree and DNS over HTTPS (DoH) on a Mikrotik Router RB951Ui-2HnD as an innovative model for achieving a “Healthy Internet” (Internet Sehat) characterised by efficiency, fairness, and safety within community-based networks. Conducted at the Infotek Hotspot in Gritma Housing, Manado, the research employed an experimental design comparing pre- and post-implementation performance over fourteen days. Key parameters measured included latency, packet loss, throughput, and DNS response time, using tools such as Wireshark, Mikrotik Bandwidth Test, and PingPlotter. The results demonstrated substantial improvements: latency decreased from 125 ms to 83 ms (−33.6%), packet loss dropped from 5.8% to 0.9% (−84.5%), and throughput increased from 36 Mbps to 49.3 Mbps (+37%). Additionally, DoH reduced DNS response time to 22 ms—13% faster than traditional DNS—while ensuring encrypted, secure, and privacy-preserving communications. These outcomes confirm that Queue Tree effectively regulates bandwidth distribution and that DoH enhances user trust through encryption and content filtering. The dual implementation forms a synergistic framework that improves network performance while upholding ethical and secure Internet usage. Furthermore, this approach offers a cost-effective and replicable solution for community hotspots, schools, and small-scale ISPs seeking stability and security without hardware upgrades. By integrating technical innovation with digital ethics, the study contributes to the development of sustainable Internet infrastructures that embody Indonesia’s Internet Sehat vision—delivering reliable, equitable, and responsible connectivity for all.